2018
DOI: 10.1002/ese3.214
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of battery modules state for electric vehicle using artificial neural network and experimental validation

Abstract: This work undertakes research problem on prediction of state of battery modules used in electric vehicle. Past studies focussed extensively on the estimation of state of charge and state of health of a single cell/battery. However, the focus on the estimation of state of entire battery module is hardly studied. During the actual operation of electric vehicle, the environmental conditions (road slope and climate) and factors such as abnormal voltage and temperature conditions causes the deviations among the bat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…The SOH estimation by the convolutional neural network, artificial neural network, and recurrent neural network are discussed in [13][14][15] respectively. The neural network has hidden layers, as the number of hidden layers is increased then computational complexity also increases with the model accuracy which is represented in fig.…”
Section: Neural Networkmentioning
confidence: 99%
“…The SOH estimation by the convolutional neural network, artificial neural network, and recurrent neural network are discussed in [13][14][15] respectively. The neural network has hidden layers, as the number of hidden layers is increased then computational complexity also increases with the model accuracy which is represented in fig.…”
Section: Neural Networkmentioning
confidence: 99%
“…A dataset consisting of 6000 samples obtained from the experiment is utilized for training and testing purposes of the DNN model. In which, each data sample includes 12 input parameters (e.g., temperature (T i ) and current This example has been previously examined by Liang et al [33] In that work, the authors used the Levenberg method to train the ANN model for predicting priority discharge of battery modules. It was found that the ANN model achieved using the Levenberg algorithm has the best with R value of 0.96 and MSE value of 0.17.…”
Section: Case Study 1: Multicell Batterymentioning
confidence: 99%
“…However, the battery is a complex electrochemical system with hardly observable or simulatable chemical reactions [5,6], so it is challenging to estimate the state of battery accurately with insufficient training data set and limited BMS calculation ability [7]. Fortunately, the development of the calculation and communication technology, especially the cloud platform [8,9] and the artificial intelligence algorithm [10], brings a bright prospect to this issue. The concept of EV cloud was proposed in [11] to collect the battery data and estimate the driving range of EVs.…”
Section: Introductionmentioning
confidence: 99%